Elitology in the Sistemof Social Sciencies - G. K. Ashin (Vestnik MGIMO-Universiteta, 2009)
The term «elitology» is a Russian innovation of the end of the 20th century. It was introduced to meet the needs of a complex discipline dealing with the elite phenomenon which integrates the achievements and methods of philosophy, political science, sociology, history, psychology, cultural studies. The article emphasizes the role of philosophy as the theoretical basis for solving elitological problems.